2010
DOI: 10.1007/s11325-010-0396-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders among undergraduate students in Southern Brazil

Abstract: Sleep alterations are prevalent complaints among young people, being present in nearly 60% of the students. Female gender and being depressed are independent factors for having some form of sleep disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…For instance in their study of Brazilian undergraduate students, Falvigna et al 32 noted that female students had a higher prevalence of sleep problems (65.7%) compared to males (54.1%). Our study results corroborate these findings as we observed a higher prevalence of poor sleep quality (56.8%) among female students, as compared with male students (52.0%).…”
Section: Discussionmentioning
confidence: 99%
“…For instance in their study of Brazilian undergraduate students, Falvigna et al 32 noted that female students had a higher prevalence of sleep problems (65.7%) compared to males (54.1%). Our study results corroborate these findings as we observed a higher prevalence of poor sleep quality (56.8%) among female students, as compared with male students (52.0%).…”
Section: Discussionmentioning
confidence: 99%
“…The present study aims to augment the understanding of sleep among Thai college students by evaluating reports of sleep hygiene and sleep quality in relation to stimulant use and other behavioral risk factors. Given prior studies [21, 22] we hypothesized that those students who use stimulants were more likely than non-users to report poor sleep quality and that this relationship may vary by sex and age.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep alterations have a high prevalence in these developing countries [12], thus, these populations are in need for alternative screening and diagnostic tools for sleep alterations [13]. None questionnaire or subjective scale is free from biases, thus we should always look for improved tools.…”
Section: Discussionmentioning
confidence: 99%